The Basis for the International Division of Labor and International Trade Is Absolute Rather than Comparative Advantage: Theory and Empirical Evidence - Xian Zhang; Jingyuan Fan (World Review of Political Economy)
According to the general consensus in academia, Ricardo’s theory of international trade embodies the theory of comparative advantage. The principle of comparative advantage he proposed, based on the model of physical trade and employing comparative cost analysis, holds that comparative advantage rather than absolute advantage forms the basis of the international division of labor and of international trade, and is thus the negation of Smith’s theory of absolute advantage. However, a complete examination of Ricardo’s theory of international trade shows that the comparative advantage determined by Ricardo on the basis of comparative cost analysis is precisely the absolute advantage of intra-sector competition across countries in physical trade. Moreover, Ricardo also established a monetary model compatible with his understanding of physical trade. This monetary model, which has generally been ignored by academics, and especially by those adhering to the mainstream, i.e., the neoclassical theory of comparative advantage, is in line with the principle of absolute advantage. In particular, Ricardo emphasized the decisive role of exogenous technological progress in altering positions of advantage. The present analysis, however, shows equally that what the neoclassical theory of comparative advantage actually proves is still absolute advantage.